Efeito da fonte e níveis de nitrogênio sobre a qualidade da silagem de trigo - Scherer, Evellyn Tainá da Silva Lemos (2024)
The objective of this study was to evaluate the bromatological composition and fermentation characteristics of pre-dried wheat silage subjected to two sources and different doses of nitrogen. The experimental design was randomized blocks, in a 2x4 factorial scheme (two nitrogen sources x four fertilization doses). Two wheat cultivars (Energix I and Energix II) were used, aimed at pre-dried production, subjected to two nitrogen sources (amide and ammoniacal nitrate) with different doses (0, 100, 200 and 300 kg of nitrogen per hectare). Nitrogen fertilization was carried out by broadcasting, divided into three applications: 25, 55 and 77 days after sowing. After 84 days of sowing, the harvest was carried out, with grain at the beginning of flowering, and subjected to pre-drying in the field, aiming to obtain around 35% of dry matter. Fifty-three individual experimental silos were made from PVC tubes measuring 30 cm in diameter and 30 cm in height, with a density of 529 ± 88.9 kg/m3 (mean ± S). After 70 days of conservation, the silos were opened and samples were taken for later evaluations. For the variables analyzed pH and ammoniacal N, increasing doses of nitrogen fertilizers linearly increased (P ≤ 0.041) the pH and ammoniacal nitrogen content of the silage, regardless of the fertilizer (P ≥ 0.784) used. There was an interaction between the quadratic effect of the N level and the type of fertilizer (P ≤ 0.031) on the DM, NDF, ADF and cellulose contents. However, intermediate doses of N from urea increased (P ≤ 0.050) the DM and NDF content in relation to the control and the highest dose (300 kg/ha). In addition, the N doses quadratically increased (P < 0.001) the CP content, regardless of the type of fertilizer (P ≥ 0.243). By quadratic regression, the highest protein content of the silage was observed with the use of 297 kg of N/ha. Thus, nitrogen fertilization increases the pH and crude protein content of wheat silage. The effect of nitrogen fertilization on the fiber content of the silage depends on the source, with an increase using intermediate doses of urea.